(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2012)
The pattern of conflict in the North Rift of Kenya involving mostly the ethnic community of the Pokot and their neighbors is a complex one. Scholars have interpreted various factors that contribute to violence and conflict in the region. These included: proliferation of illegal arms, inadequate policing and state security arrangements, diminishing the role of the traditional government, competition over control and access to natural resources such as pasture-land and water, political incitements, ethnocentrisms, increasing level of poverty, idleness among the youth, and territorial control. The concept of the Pokot culture however has been inadequately explored. Culture, taken in a broader sense, is the way of life of a people as Mary Clark puts; “it includes socially acquired knowledge, beliefs, art, law, morals, customs, and habits … Culture is a life thought system, which influences the people’s lives, activities and behavior towards others”. A cattle rustling is a cultural aspect of the Pokot founded on their myth of origin and a belief that all cattle belong to them. This research hypothesizes that the cultural belief in raiding is perpetuated by people (seers) who have an economic and political interest in promoting the very cultural system that places them in a powerful position.